Human Capital And SME Performance: In Collaboration With Catur Paramitha-Based Entrepreneurship Orientation Value - Indrawati, Ayu; Triaryati, Nyoman (Universitas Pendidikan Nasional, 2024)
This study examines the moderating effect of entrepreneurial orientation values based on Catur Paramitha on the relationship between human capital and the performance of small and medium enterprises (SMEs) in Bali. This research is motivated by inconsistencies in empirical findings regarding the influence of human capital on SME performance, highlighting the need for integrating local perspectives into the research model. The respondents of this study consist of 300 formal-sector SMEs registered with the Department of Cooperatives and SMEs of Bali Province. Primary data, including both quantitative and qualitative types, were analyzed using a structural model approach with Partial Least Square (PLS). The findings reveal that human capital significantly positively affects SME performance. Furthermore, entrepreneurial orientation values based on Catur Paramitha (encompassing the values of Maitri, Karuna, Mudita, and Upeksa) serve as a moderating variable that strengthens the relationship between human capital and SME performance. These findings not only reinforce the Resource-Based View (RBV) theory but also provide practical contributions. Implementing Catur Paramitha values can assist SMEs in becoming more humanistic, ethical, and collaborative organizations. By integrating these local values, Bali SMEs are expected to sustainably enhance their performance while preserving the uniqueness of their cultural heritage. This study also underscores the importance of local wisdom as a guiding principle for SMEs to operate ethically and with dignity, creating a competitive advantage in the global marketplace.